2008
DOI: 10.1038/cgt.2008.10
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-targeting prodrug-activating bacteria for cancer therapy

Abstract: Increasing the specificity of chemotherapy may improve the efficacy of cancer treatment. Toward this aim, we developed a strain of bacteria to express enzymes for selective prodrug activation and non-invasive imaging in tumors. b-glucuronidase and the luxCDABE gene cluster were expressed in the DH5a strain of Escherichia coli to generate DH5a-lux/bG. These bacteria emitted light for imaging and hydrolyzed the glucuronide prodrug 9ACG to the topoisomerase I inhibitor 9-aminocamptothecin (9AC). By optical imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 38 publications
0
36
0
1
Order By: Relevance
“…10,11 However, the most frequently used anti-cancer approach using bacteria is enzyme-prodrug therapy where systemically administered bacteria are used to deliver a gene/enzyme able to convert systemically administered prodrug into its active compound specifically in tumor tissue. [12][13][14] The utilization of bacterial systems for therapeutic purposes is further enhanced by genetic modifications, which make them a very promising tool for targeted delivery of genes and their products. Specific advantages of using bacteria for anti-cancer gene therapy include the natural oncolytic potential of some strains/species, direct targeting of tumor tissue and the ease of positive regulation/eradication.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 However, the most frequently used anti-cancer approach using bacteria is enzyme-prodrug therapy where systemically administered bacteria are used to deliver a gene/enzyme able to convert systemically administered prodrug into its active compound specifically in tumor tissue. [12][13][14] The utilization of bacterial systems for therapeutic purposes is further enhanced by genetic modifications, which make them a very promising tool for targeted delivery of genes and their products. Specific advantages of using bacteria for anti-cancer gene therapy include the natural oncolytic potential of some strains/species, direct targeting of tumor tissue and the ease of positive regulation/eradication.…”
Section: Introductionmentioning
confidence: 99%
“…E. coli is part of the flora of the human GIT. Several studies have outlined the safety of IV administration of non-pathogenic E. coli strains to mice, and their ability to grow specifically within tumors 4,12 . E. coli MG1655 (as used in this study) also colonizes the mouse GIT to high levels 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Although methods for efficient enrichment of cancers by βG are still needed, several techniques are under development to preferentially accumulate βG in tumors, including antibody-directed enzyme prodrug therapy (22,27), genedirected enzyme prodrug therapy (19,20), and targeted bacterial expression of Escherichia coli βG (28). In addition, mutant human βG enzymes that display enhanced enzymatic activity at neutral pH values are being developed for selective activation of glucuronide drugs in tumors (33).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we tested the hypothesis that endogenously generated SN-38G is present in tumors at sufficient levels to contribute to the antitumor effects of CPT-11 therapy if it is reconverted to SN-38. As a model system, we used EJ human bladder cancer cells engineered to express membrane-tethered βG on their surface (EJ/mβG cells) to mimic the clinically relevant situations in which interstitial βG activity is naturally high (17) or artificially elevated by antibody, gene, or bacterial delivery methods (19,20,22,26,28). We found that after CPT-11 treatment, reconversion of endogenously produced SN38G to SN-38 in EJ/mβG bladder tumors significantly enhanced the anticancer efficacy of CPT-11.…”
Section: Discussionmentioning
confidence: 99%